CHEWING GUM TO HASTEN BOWEL RECOVERY IN CESAREAN SECTION: A RANDOMIZED CONTROL TRIAL - Zainab, Sadia; Akbar, Amina; Mahboob, Saira; Munir, Shazia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the recovery of bowel function by chewing gum in comparison with standard care.Study Design: Randomized control trial (RCT).Place and Duration of Study: Department of Gynecology and Obstetrics, Combined Military Hospital, Okara Cantt for the duration of 6 months from Apr to Sep 2018.Methodology: After the approval of hospital ethics committee, 100 patients undergoing elective cesarean section were divided into two groups (n=50 in each group). Group A were told to chew gum for 1 hour, four hours postoperatively in addition to standard care. Group B were the control group, with no addition of chew gum. The data were analyzed by SPSS version 20. Qualitative data presented as frequency and percentage; chi-square used to calculate significance. Descriptive data were presented as mean ± SD; T-test used to calculate significance. A p-value less than 0.05 was taken as significant.Results: The two groups did not vary in their demographic profile. The mean time for auscultation of bowel sound was 6.5 hours ± 1.03 in group A versus 9.3 hours ± 1.56 in group B; p-value